2015
DOI: 10.1016/j.cardfail.2015.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Resynchronization Therapy Induces Adaptive Metabolic Transitions in the Metabolomic Profile of Heart Failure

Abstract: Background Heart failure (HF) is associated with ventricular dyssynchrony and energetic inefficiency, which can be alleviated by cardiac resynchronization therapy (CRT). The aim of this study was to determine the metabolomic signature in HF and its prognostic value for the response to CRT. Methods This prospective study consisted of 24 patients undergoing CRT for advanced HF and 10 control patients who underwent catheter ablation for supraventricular arrhythmia but not CRT. Blood samples were collected befor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 59 publications
2
40
0
1
Order By: Relevance
“…27 Furthermore, examination of plasma metabolomic profiles showed that patients with HF who respond to cardiac resynchronization therapy have higher baseline levels of BCAAs (including valine, leucine, isoleucine, and phenylalanine) and lower glutamate levels than non-responders. 52 Although BCAAs appear to have therapeutic potential against HF, there is also evidence of a pathological role in cardiac metabolic dysfunction. It was recently reported that Krüppel-like factor 15 suppressed BCAA catabolism in a murine HF model, with impairment of BCAA catabolism reducing cardiac function and promoting HF in the setting of LV pressure overload, together with elevated superoxide production and cardiac metabolic remodeling.…”
Section: Metabolites Of Glycolysis and The Tca Cyclementioning
confidence: 99%
“…27 Furthermore, examination of plasma metabolomic profiles showed that patients with HF who respond to cardiac resynchronization therapy have higher baseline levels of BCAAs (including valine, leucine, isoleucine, and phenylalanine) and lower glutamate levels than non-responders. 52 Although BCAAs appear to have therapeutic potential against HF, there is also evidence of a pathological role in cardiac metabolic dysfunction. It was recently reported that Krüppel-like factor 15 suppressed BCAA catabolism in a murine HF model, with impairment of BCAA catabolism reducing cardiac function and promoting HF in the setting of LV pressure overload, together with elevated superoxide production and cardiac metabolic remodeling.…”
Section: Metabolites Of Glycolysis and The Tca Cyclementioning
confidence: 99%
“…Other sources of data such as genomic, metabolomic or other biomarker information may also be additive to a global model of risk. For example, recent studies have demonstrated that metabolomics may not only be diagnostic for heart failure, but also predictive of responses to cardiac resynchronization and ICD therapies [49][50][51][52]. Integrating electrobiochemical 'omic information may yield further predictive information, which cannot be yielded by any individual method separately [53,54].…”
Section: Discussionmentioning
confidence: 99%
“…Systolic heart failure is also associated with inter-and intraventricular conduction disturbances and dyssynchrony, which are responsible for further impairment in systolic function. Nemutlu et al [100] indicated that resynchronization therapy (CRT) may improve plasma metabolic profile within the most important metabolites, including fatty acids, amino acids, lipids and Krebs cycle intermediates. Nevertheless, there were still some metabolites the level of which did not restore to the normal range, suggesting an existence of CRT-independent metabolic disturbances or pathways [100].…”
Section: Potential Implications For the Treatment Of Heart Failurementioning
confidence: 99%